2022
DOI: 10.1155/2022/3409693
|View full text |Cite|
|
Sign up to set email alerts
|

A Study on Risk Factors Associated with Reflux Esophagitis in Patients Undergoing Esophageal Cancer Surgery

Abstract: Objective. To investigate the risk factors associated with reflux esophagitis in patients undergoing esophageal cancer surgery and to provide reference for the prevention and treatment of reflux esophagitis. Methods. In the manner retrospective study, the data of 300 patients with esophageal cancer who received the surgical treatment in our hospital (January 2018–December 2020) were retrospectively reviewed. The 300 patients were divided into the occurrence group (n = 45) and nonoccurrence group (n = 255) depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Journal of Healthcare Engineering has retracted the article titled "A Study on Risk Factors Associated with Refux Esophagitis in Patients Undergoing Esophageal Cancer Surgery" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Healthcare Engineering has retracted the article titled "A Study on Risk Factors Associated with Refux Esophagitis in Patients Undergoing Esophageal Cancer Surgery" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “A Study on Risk Factors Associated with Reflux Esophagitis in Patients Undergoing Esophageal Cancer Surgery” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%